(untitled) (Texas Journal of Medical Science, 2022)
Pain is an unpleasant sensory and emotional experience associated with actual or perceived tissue damage. (World Health Organization. International Classification of Diseases 11th Revision. Geneva: World Health Organization; 2019). Postoperative pain of varying intensity occurs after any operation, both after minimal outpatient interventions and after highly traumatic hours-long operations. Postoperative pain is not just an acute pain syndrome, it is also a strong trigger of the surgical stress response, which causes the activation of the autonomic nervous system and has a negative impact on almost all vital organs and systems.